Pengaruh Bimbingan Guru Di Kelas Terhadap Motivasi Belajar Siswa Pada Kelas XI Program Keahlian Akuntansi Di SMK Negeri 7 Makassar - Atika, Nurul; Sahade, Sahade; Hasyim, Sitti Hajerah (EDUKASI, 2023)
The research carried out the aim ofÂ  analyzing Â the impact of instructor direction in lesson on students' learning inspiration in lesson XI of the Bookkeeping Aptitudes Program at SMK Negeri 7 Makassar. The factors in this investigate are educator direction as the free variable and learning inspiration as the subordinate variable. The populace is all Lesson The testing procedure utilized proportionate stratified arbitrary testing strategy with a test of 53 understudies taken haphazardly and relatively. The information collection methods utilized were surveys and documentation. The information investigation strategy utilized is instrument testing comprising of legitimacy and unwavering quality tests, speculation testing comprising of straightforward straight relapse examination, coefficient of assurance, and t test utilizing SPSS form 25 for Windows.Based on the comes about of the information examination that has been carried out, a straightforward straight relapse condition show is gotten, Y=31.066+0.350X, which suggests that for each extra 1 educator direction esteem, the learning inspiration esteem increments by 0.350. From the comes about of the investigation of the coefficient of assurance (r2), the esteem of r2 = 15.4% is gotten, which suggests that instructor direction has an impact on learning inspiration of 15.4% and the remaining 84.6% is impacted by other components. In the interim, from the comes about of the t-test investigation, a noteworthy value of 0.0040.05 was gotten, which suggests that educator direction contains a noteworthy impact on learning inspiration, in this way the theory is acknowledged.